The influence of childhood exercise and health gains for the future (Research, Society and Development, 2022)
Introduction: Childhood is one of the most significant parts of your child's health, as essential processes in growth and development take place during this period/phase. In order to help support the population to achieve the goals and maintain a healthy daily life, all countries are notified by the World Health Assembly (WHA) to develop a policy implementation of national and subnational programs, in order to authorize people of ages and with diverse abilities, are physically active and healthy. Thus, this study aimed to address and report the benefits of physical activity developed in childhood and adulthood, the importance of an active life, the assumptions and risks of having a sedentary life. Methodology: this is an exploratory, bibliographic research using scientific articles available in the databases of journals, such as: BVS, Fiocruz, Faculdade AGES, Google School, Instituto IDEIA, IFC, LILACS, Multidisciplinary Reviews, PUC Goiás, PubMed, Revista Multidisciplinary Science Center for Knowledge, REASE, SCIELO, UPF, UFSM, USP, WHO. Results and Discussions: Regardless of the period in which it is, physical activity can present numerous benefits for the practitioner, for example, improving the growth of children, influencing the achievement of a good quality of life and health. Physical activity is a process that, together with the environment, nutrition and genetics, helps the individual to reach his/her potential for growth and development, to develop, absolutely, physical capacity and have, in the result, a favorable level of health. . Conclusion: Physical activity is indicated for any age group in a process that acts directly on the child's motor development, in the fight against sedentary lifestyle, which makes them more active, as long as it is carried out with the accompaniment of a qualified professional (Physical Educator).